High performance of straight and U-shaped probe microfiber sensors for sucrose solution detection applications - Apsari, Retna; Zulkarnaen, M; Na'imah, Syahidatun; Trilaksana, Herri; Yasin, M; W. Harun, Sulaiman (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2024)
A low cost, highly sensitive sensor with easy fabrication has been successfully developed to detect variations in the concentration of sucrose solutions using a microfiber probe sensor. The microfiber probe was fabricated using a flame brushing mixture of butane and oxygen with single-mode optical fiber material and pulled on both sides to achieve a size of 16.48 µm. These microfiber probes were characterized into two sensor probe shapes: straight and u-shaped, to measure variations in the sucrose solution concentration. The results for both probe shapes showed a decrease in peak output intensity and a shift in peak wavelength as the sucrose concentration increased from 0.5% to 3%. The straight shape exhibited a sensitivity of 0.241 dBm/% with a slope linearity of 99.5% and a resolution of 0.0415%, while the U-shape had a sensitivity of 2.692 dBm/% with a slope linearity of 90.6% and a resolution of 0.0030%. The measurement spectra results indicated significant differences in u-shape at each concentration. In conclusion, both microfiber sensor probe shapes exhibited excellent performance and are suitable for use as chemical sensors to measure variations in solutions.